Evaluation of canal transportation after root canal instrumentation a comparative in vitro study with cone-beam computed tomography - Aditi Jain; Asmita Singh Gupta (Wolters Kluwer Medknow Publications, 2019)
Aim: Reciproc and WaveOne (WO) system was used to evaluate the canal centering ability and apical transportation by cone-beam computed tomography. Materials and Methods: Forty extracted human single-rooted mandibular premolars were used in the present study. Preinstrumentation scans of all teeth were taken; canal curvatures were calculated; and the samples were randomly divided into two groups with 20 samples in each group, where Group 1-Reciproc system and Group 2-WO reciprocation system. Postinstrumentation scans were performed using DICOM software and the two scans were compared to determine centering ability and canal transportation at 3, 6, and 9 mm from the root apex. Results: Using Student's unpaired t-test results were as follows, for centering ability Group 1 showed nonstatistically significant difference at 3 mm and 9 mm, whereas a statistically significant difference (P < 0.05) at 6 mm was obtained. For canal transportation, Group 1 showed a statistically significant difference (P < 0.05) at 3 mm and 6 mm, and nonsignificant difference was obtained at 9 mm, but for Group 2, nonstatistically significant difference (P > 0.05) was obtained at 3 mm, 6 mm, and 9 mm. Conclusion: WO single reciprocation file has better centering ability, maintains original canal curvature, and causes lesser canal transportation as compared to reciproc.